Cortical hand bone loss after 1 year in early rheumatoid arthritis predicts radiographic hand joint damage at 5-year and 10-year follow-up. Issue 3 (13th March 2008) - Hoff, M; Haugeberg, G; Ødegård, S; Syversen, S; Landewé, R; van der Heijde, D; Kvien, T K
Abstract : Objective: To examine 1-year hand bone loss in early rheumatoid arthritis (RA) as a predictor of radiographic damage at 5-year and 10-year follow-up Methods: A total of 136 patients with RA (disease duration 0–4 years) were followed for 10 years with clinical data and hand radiographs. Joint damage was scored according to the van der Heijde modification of the Sharp method (vdH Sharp score) and hand bone mineral density (BMD) was measured by digital x ray radiogrammetry (DXR). Group comparisons, correlation analyses and multivariate analyses were performed to evaluate the relationship between hand bone loss and radiographic joint damage. Results: Patients with hand BMD loss at 1 year had a higher median increase in vdH Sharp score compared to patients without loss at 5 years (12 vs 2, p = 0.001) and 10 years (22 vs 4, p = 0.002). In a linear regression model adjusting for age, gender, baseline C-reactive protein (CRP), anti-cyclic citrullinated peptide (CCP), IgM rheumatoid factor (RF) and radiographic damage, absolute hand DXR-BMD loss at 1 year was an independent predictor of radiographic outcome at 5 years (p<0.01) and 10 years (p = 0.02). In a logistic regression model the odds ratio (95% CI) for radiographic progression among patients with hand BMD loss was 3.5 (1.4 to 8.8) and 3.5 (1.4 to 8.4) at 5 and 10 years, respectively. Conclusion: Early hand bone loss measured by DXR-BMD is an independent predictor of subsequent radiographic damage. Our findings support that quantitative hand bone loss in RA precedes radiographic joint damage and may be used as a tool for assessment of bone involvement in RA.